Programming in Modula-2 - Daoust A. David; Dedourek M. John; Tremblay Paul-Jean (Mcgraw Hill Book Company, 1989)
Computer Science Series. Preface, Introduction to Modula-2 Programming, Fundamental Modula-2 Concepts, Decision Structures, Subprograms, Composite Data Structures, String Manipulation, The Engineering of Computer Software, Linear Data Structures, Non Linear Data Structures, Files, Index.